Hypothetical versus actual support providers in comparative network research - Hlebec, Valentina (Metodološki zvezki, 2005)
Informal social networks are the most important source of social support, which is an essential foundation for the quality of everyday life. Distributions of various types of social networks have to be studied from a comparative perspective to evaluate the effects of the change in political, social and economic systems in Slovenia on social network composition and structure. Data from two studies are compared: one made before (1987) and one after the transition (2002) on representative samples of adult residents of Slovenia. In the paper the ability of informal social networks to provide an adequate sources of social support is discussed as the substantive part of this research. The effects of characteristics of the measurement instruments (hypothetical versus actual support providers) on obtained estimates of network composition are presented and evaluated. The advantages and disadvantages of the relationship approach to measuring personal networks are discussed with regard to complete evaluation of network membership.
Keywords: Družbena omrežja; Social networks; Analiza omrežij; Network analysis; družboslovno raziskovanje